2014
DOI: 10.1007/s00277-014-2270-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and evaluation of three screening tests of hereditary spherocytosis in Chinese patients

Abstract: The objective of this study is to compare and evaluate the diagnostic value of hereditary spherocytosis (HS) by three screening tests, comparing mean spherical corpuscular volume (MSCV) to mean corpuscular volume (MCV), mean corpuscular hemoglobin concentration (MCHC), and flow cytometric osmotic fragility test. Peripheral blood was collected from 237 participators diagnosed at the First Affiliated Hospital of Guangxi Medical University, including 56 hereditary spherocytosis patients, 86 thalassemia patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 20 publications
2
19
0
1
Order By: Relevance
“…The cutoff determined for %RRC in the present study was 25.7% and is comparable to the cutoff values reported by Warang et al, Crisp et al, and Tao et al Park et al reported a lower cutoff value of 6.6% as they did not apply the dilution factor. Even if the same dilution factor is applied to this cutoff, the value will be ~12% which is lower than that the cutoffs reported earlier and the present study. The cutoff reported by Shim et al is much higher at %RRC 61.9% and may be due to the different ethnicity of the patients.…”
Section: Discussionsupporting
confidence: 89%
“…The cutoff determined for %RRC in the present study was 25.7% and is comparable to the cutoff values reported by Warang et al, Crisp et al, and Tao et al Park et al reported a lower cutoff value of 6.6% as they did not apply the dilution factor. Even if the same dilution factor is applied to this cutoff, the value will be ~12% which is lower than that the cutoffs reported earlier and the present study. The cutoff reported by Shim et al is much higher at %RRC 61.9% and may be due to the different ethnicity of the patients.…”
Section: Discussionsupporting
confidence: 89%
“…In 1999, Chiron et al first reported the diagnostic value of MSCV and MCV for HS, with MSCV < MCV showing 100% diagnostic sensitivity and 93.3% specificity for HS. Broséus et al used MCV‐MSCV > 9.6 fl as a standard, corresponding to 100% diagnostic sensitivity and 90.57% specificity for HS, while Tao et al . reported that MSCV < MCV had a sensitivity of 89.28% and a specificity of 96.14% for the diagnosis of HS.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, recent studies have verified that mutations in SLC4A1 and SPTA1 are not specific to HS patients [4, 48, 49]. To identify different types of hemolytic anemia and hepatitis, clinical histories and laboratory tests are needed [3, 4, 48-51]. Ribeiro et al [52] reported that, in the case of some mutations that can be inherited and lead to severe HS, genetic counseling and prenatal diagnosis can play an extremely important role in prenatal and postnatal care.…”
Section: Summary and Prospectsmentioning
confidence: 99%